Economic Policy Uncertainty and Firm Value: Is There a Link? A Panel Vector Autoregression Approach - Olalere, Oluwaseyi Ebenezer (Animo Repository, 2022)
This study examines the effect of the economic policy uncertainty (EPU) index on firm value. The financial data of 105 conventional banks for BRICS (Brazil, Russia, India, China, and South Africa) countries over 2009–2019 were used, totaling 1,155 observations. We use the panel vector autoregression estimate, and the results show that EPU can predict the firm value of conventional banks. When we use the generalized method of moments (GMM) estimates, the findings indicate that EPU has a significant impact on BRICS countries’ firm value. The GMM analysis confirms the prediction of the panel vector autoregression that the EPU index with other firm-specific and macroeconomic variables significantly affects firm value. This study presents a unique and significant implication by focusing on financial institutions where there have been limited empirical studies. Advanced analytical techniques are conducted in the study over a long time using recent data.